Attending Operating Rooms for Clinical-Years Medical Students: Benefits and Barriers - Al-Taher, Raed; Rashdan, Mohammad; Amarin, Marzouq; Addasi, Rami; Odeh, Ghada; Abu-Harb, Amal; Habashneh, Rawan; Al-Omari, Dana; Al-Zughayer, Lubna; Toukan, Rama; Al-Awamleh, Renad; Qasho, Sanaa (Jordan Medical Journal, 2023)
Background and Aim: Attending operations is part of medical school education. This research studied the benefits and barriers facing students in the operating theaters. It also looked for student, surgeon and environmental factors that could play a role in participants’ understanding. The aim was to explore the effect on participants’ perception and understanding of surgical techniques to shed light on the obstacles faced, and whether the learning objectives, either in general surgery or sub-surgery courses, can be achieved. Materials and Methods: This cross-sectional, questionnaire-based study used an electronic questionnaire (Google Forms), and 287 responses were received. Data were then analyzed using SPSS software. Results: Of the 287 medical students who completed the questionnaire, 83% of those who scrubbed-in confirmed that scrubbing-in and being part of the operating team provided them with a better understanding. Laparoscopic-type surgeries carried a better teaching benefit. Neither the number of students attending the theatre, attendance at previous surgical skills courses, or the future specialty interest of the medical student had a significant correlation with the benefit of attending the operating rooms. Our findings align with those of many other studies, in that the main points are the role of the surgeon, the environment, and the importance of scrubbing-in. Conclusion: A surgeon who provides good explanations and a student who knows the learning goals before going to the theatre, as well as a friendly environment, were found to achieve the best combination with the best outcome.